2009
DOI: 10.1089/thy.2008.0295
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Iodide Excess and Interferon-γ on Human Primary Thyroid Cell Proliferation, Thyroglobulin Secretion, and Intracellular Adhesion Molecule-1 and Human Leukocyte Antigen-DR Expression

Abstract: Augmented ICAM-1 in the presence of iodide excess and low-dose IFN-gamma could induce secretion of proinflammatory cytokines and lymphocytic infiltration in the thyroid gland. Decreased Tg production in the presence of KI excess and IFN-gamma could explain the development of hypothyroidism after adding iodide in a diet of subjects that already have lymphocytic infiltration and/or mild inflammation in the thyroid gland.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 48 publications
(48 reference statements)
0
11
1
Order By: Relevance
“…Other studies also showed that 0.1 rnM of KI in the presenee of IFN-y additionally increased lCAM-1 expression, another important eostimulatory molecule [12,16]. We didn't observed the influence of iodine on the CD40 expression in basal condition, however, we observed that at the concentration of 0.001 mM 0.2 mM, potassium iodide could obviously upregulate the expression of CD40 induced by IFN-y.…”
Section: Discussioncontrasting
confidence: 75%
See 2 more Smart Citations
“…Other studies also showed that 0.1 rnM of KI in the presenee of IFN-y additionally increased lCAM-1 expression, another important eostimulatory molecule [12,16]. We didn't observed the influence of iodine on the CD40 expression in basal condition, however, we observed that at the concentration of 0.001 mM 0.2 mM, potassium iodide could obviously upregulate the expression of CD40 induced by IFN-y.…”
Section: Discussioncontrasting
confidence: 75%
“…Sorne transient effect had been reported on other studies about a relatively high dose of KI on the IFN-y induced MHC Class II expression [12]. Tliere is no effect of iodine on IFN-y induced HLA-DR expression either.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…These results indicated that excessive iodide exposure may cause nervous system impairment and ultimately induce intellectual damage, which was consistent with Zhao's study . Additionally, the concentrations used in our study were chosen based on the cytotoxic effects derived from the CCK‐8 trial, which were largely consistent with other reports investigating the toxic effects of excessive iodine on human thyroid cells …”
Section: Discussionmentioning
confidence: 87%
“…Furthermore, iodide excess did not change Tg level in FRTL-5 cells (Pregliasco et al, 1996), but it inhibited iodine organification (Davies et al, 1989), thyroid hormone secretion (Sato et al, 1990), and cAMP production and secretion (Miyazaki et al, 1999) in isolated human thyroid follicles. Recently, it was reported (Kostic et al, 2009) that iodide excess inhibited human primary thyroid cell proliferation and gradually increased ICAM-1 on cell surface. In the presence of low-dose IFN-gamma, KI additionally augmented ICAM-1 expression, and such effect could induce lymphocytic infiltration in the thyroid gland and secretion of proinflammatory cytokines.…”
Section: The Possible Role Of Iodide Excess On Thyroid Mild Inflammatmentioning
confidence: 99%